Limbic and Basal Ganglia Neuroanatomical Correlates of Gait and Executive Function: Older Adults With Mild Cognitive Impairment and Intact Cognition. (April 2018) - McGough, Ellen L.; Kelly, Valerie E.; Weaver, Kurt E.; Logsdon, Rebecca G.; McCurry, Susan M.; Pike, Kenneth C.; Grabowski, Thomas J.; Teri, Linda
Abstract : Objective: This study aimed to examine differences in spatiotemporal gait parameters between older adults with amnestic mild cognitive impairment and normal cognition and to examine limbic and basal ganglia neural correlates of gait and executive function in older adults without dementia. Design: This was a cross-sectional study of 46 community-dwelling older adults, ages 70–95 yrs, with amnestic mild cognitive impairment ( n = 23) and normal cognition ( n = 23). Structural magnetic resonance imaging was used to attain volumetric measures of limbic and basal ganglia structures. Quantitative motion analysis was used to measure spatiotemporal parameters of gait. The Trail Making Test was used to assess executive function. Results: During fast-paced walking, older adults with amnestic mild cognitive impairment demonstrated significantly slower gait speed and shorter stride length compared with older adults with normal cognition. Stride length was positively correlated with hippocampal, anterior cingulate, and nucleus accumbens volumes ( P < 0.05). Executive function was positively correlated with hippocampal, anterior cingulate, and posterior cingulate volumes ( P < 0.05). Conclusions: Compared with older adults with normal cognition, those with amnestic mild cognitive impairment demonstrated slower gait speed and shorter stride length, during fast-paced walking, and lower executive function. Hippocampal and anterior cingulate volumes demonstrated moderate positive correlation with both gait and executive function, after adjusting for age. To Claim CME Credits: Complete the self-assessment activity and evaluation online athttp://www.physiatry.org/JournalCME CME Objectives: Upon completion of this article, the reader should be able to: (1) discuss gait performance and cognitive function in older adults with amnestic mild cognitive impairment versus normal cognition, (2) discuss neurocorrelates of gait and executive function in older adults without dementia, and (3) recognize the importance of assessing gait speed and cognitive function in the clinical management of older adults at risk for dementia. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 0.5 AMA PRA Category 1 Credit(s) ™. Physicians should only claim credit commensurate with the extent of their participation in the activity. Abstract : Supplemental digital content is available in the text.